New perspectives onto the metal–to–non-metal transition in expanded liquid metals. (28th June 2018) - Pilgrim, W.-C.; Szubrin, D.; Demmel, F.; Orecchini, A.; Rols, S.; Laloni, A.; De Francesco, A.
Abstract: The collective dynamics of liquid rubidium was measured by inelastic neutron scattering from melting up to 1673 K and 6.4 MPa to explore an electron gas instability, forecasted by theory at sufficient expansion. Pronounced variations are observed when the predicted conditions are approached. They comply with a scenario for the density-driven metal–to–non-metal transition suggested for fluid mercury where the liquid metal decomposes into a nanoemulsion of metallic and non-metallic domains and the metallic domains constantly disappear with ongoing expansion. Collective modes appear as an unambiguous signature of the metallic phase allowing to directly observe this process.